H.M. Misimer’s Letter to Martha Misimer August 8, 1864 - Wheeler, Joseph A. (2022)
This document is a transcription of a letter written July 13, 1864 and sent by Henry M. Misemer, also known as H. M. Misemer, to his wife Martha J. Misemer. Misemer was from Monroe County east Tennessee. Prior to the American Civil War, he was a farmer, and his land was valued at $1000. During the civil war he served in the Union’s 3rd Regiment of the Tennessee Calvary in Company F. He was a Trumpeter, Private, and Corporal. East Tennesseans, like Misemer, did not align themselves with the Confederacy and instead opposed a receding from the Union. Slavery had been all but abolished in East Tennessee, with most of its residents being too poor to afford slaves. Misemer and Margaret J. Brown married on January 25th, 1855. They had one daughter together, Mary E. Misemer. Margaret would die in August 1857. Martha J. Bogart was married to H. M. Misemer on February 2nd, 1859. They had 3 children together, these were Charles F. Misemer, Margaret E. Misemer, and Laura C. Misemer. The East Tennessee community was largely devout Christians, due in some part to the sizable Quaker community that moved there in the early 19th century. This transcription and its attendant annotations, explanatory material, and bibliography were prepared by students in ENGL 618: Research Methods in English, the required gateway class for the MA in English at Western Carolina University.